Hybrid Sharia Contracts for Economic Justice: A Critical Evaluation of Mudharabah Musytarakah and Murabahah Practices in the Amm Burger & Coffee Business - Amanda Shaafia Malik; Muhammad Hilman Maulana; Lutfhi Helmi; Dwi Aprilianti; Luthfi Faisal Hermawan; Dimas Sulistyo Farras (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
This study examines the implementation of hybrid Islamic finance contracts, Mudharabah, Musytarakah, and Murabahah, in promoting economic justice within the Amm Burger & Coffee MSME business model. Using a mixed-methods approach that integrates surveys, financial documentation, and in-depth interviews, the research evaluates how these multi-contract schemes strengthen capital, distribute risks, and ensure transparency in business operations. The findings indicate that the Mudharabah Musytarakah partnership constitutes a fair and proportional profit-sharing mechanism, consistent with the principles of mutual consent and justice in Islamic commercial law. Loss allocation was carried out appropriately, with capital-contributing partners bearing financial risks in proportion to their investments. At the same time, the manager assumed non-financial responsibilities, including time, effort, and operational accountability. In external transactions, Murabahah agreements with meat and coffee suppliers fully complied with Sharia requirements, including the clarity of cost, profit margin, ownership transfer, and product quality. Although minor discrepancies occurred with the bread supplier regarding product specifications, the issue was resolved through deliberation, demonstrating the effectiveness of sharia-based dispute resolution. Overall, the study concludes that applying Mudharabah Musytarakah and Murabahah contracts simultaneously can achieve a balanced integration of economic, ethical, and legal principles, offering a practical and justice-oriented financing model for MSMEs. This hybrid contract structure has strong potential to serve as a scalable prototype for inclusive Islamic economic development in Indonesia.